[PP.11.05] PATIENTS WITH ESTABLISHED CV DISEASE HAD HIGHER PREVALENCE OF SEVERAL RISK CV INDICATORS, WHEN COMPARED TO HIGH CV RISK POPULATION WITHOUT PREVIOUS EVENT. (September 2017) - Pires, J.; Pinto, S.; Teixeira, M.; Ferreira, F.; Ribau, V.; Neves, C.; Mesquita Bastos, J.
Abstract : Objective: Pulse wave velocity (PWV) is considered a marker of cardiovascular (CV) risk prognosis. In a hypertensive population, higher values are associated with an elevated CV risk and higher risk of events. However, the difference between patients with high CV without CV event, and those with established CV disease (defined by heart failure that implies hospital admission, coronary heart disease, stroke, peripheral artery disease) is not very defined. The authors aim to characterize a hypertensive population who was submitted to PWV and to identify features which could differentiate high CV risk population with or without previous event. Design and method: 280 hypertensive medicated patients were studied. Continuous variables are expressed as mean and were compared using the unpaired Student's t-test. Variables exhibiting skewed distributions are expressed as median and interquartile range and were compared using the Mann-Whitney test. Categorical variables are expressed as frequencies and percentages and were compared using the chi-squared test. Results: Considering the 280 patients, the mean age was 52.94 ± 15.35 years, mean BMI was 28.21 ± 4.73 Kg/m 2, mean SBP24 hours was 125.82 ± 11.59 mmHg, mean PWV was 8.93 ± 2.44. Fifty six patients had previous events. This group, when compared with those patients without previous event, were older (61.70 ± 9.27 years versus 50.75 ± 15.79), had a higher PWV (9.64 ± 2.13 versus 8.75 ± 2.49), higher prevalence of diabetes (32.1% versus 21.0%, p = 0.07) and dyslipidemia (73.2% versus 54.9%, p = 0.013). Also 41.1% of patients with previous event had PWV > 10 m/s and only 23.7% of the patients without previous events had PWV > 10 m/s (p = 0.009). Other risk indicators were also more prevalent in the established cardiovascular disease population, although without statistical significance: smoking (16.1% versus 12.1%, p = 0.423) and diastolic dysfunction (40% versus 33.3%, p = 0.472). Conclusions: In our sample, patients with established CV disease had higher prevalence of several risk CV indicators, when compared to high CV risk population without previous event, pointing to a higher risk of recurrence of event when comparing with patients with high risk, but no previous event. The strict control of CV risk factors in this population is mandatory.